Tetralogy of Fallot Associated with Dysplastic Kidneys, Cloacal Anomalies, and Female Pseudohermaphroditism: A Systemic Anomaly of Septation? - José Morales-Roselló; Teresa Escudero Serrano; Ana García Almela; Rafael Lázaro Santander (Case Reports in Obstetrics and Gynecology)
A 20-week fetus was diagnosed with tetralogy of Fallot and multicystic kidneys. The postmortem study showed missing müllerian structures with small streak ovaries, external male genitalia, and an abnormal cloacal septation (imperforate anus with a sigmoid colon opening in the bladder). As the observed anomalies were related with septation, a mechanism related with the activation of specific growth factors, we discuss the possibility of a disorder in the function of the bone morphogenetic proteins as a common cause for the widespread anomalies found in this fetus.